2020
DOI: 10.13187/me.2020.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Gender Stereotyping in Fashion Advertising: A Perceptual Analysis of Male Consumers from Pakistan

Abstract: This study is aimed at answering the male perception about gender related stereotypes that make up major part of printed fashion advertisements. Carried out on Pakistani men, this paper attempts to fill the research gap related to how gender stereotypes are perceived by men as consumers of printed fashion advertising. In-depth, semi-structured interviews were carried out with Pakistani men who shop for their own clothing. The empirical data was coded manually. The findings revealed a positive attitude of men t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Most of the study participants were found to be females that felt greatly attach to certain brands of clothing, shoes, and makeup and felt jealous when they are not able to purchase the specific brand due to financial restrictions, product availability, or cultural norms. But they aspire to certain brands and see their potential customers as rivals (Mazahir et al, 2020). These brands include some local and most international brands, such as Ferrari and Audi in cars, Huda Beauty, and NARS in Makeup, M&S (marc and spencer), Khadi, Sapphire, Crimson, Suffuse by Sana Yasir for women clothing (Abrar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the study participants were found to be females that felt greatly attach to certain brands of clothing, shoes, and makeup and felt jealous when they are not able to purchase the specific brand due to financial restrictions, product availability, or cultural norms. But they aspire to certain brands and see their potential customers as rivals (Mazahir et al, 2020). These brands include some local and most international brands, such as Ferrari and Audi in cars, Huda Beauty, and NARS in Makeup, M&S (marc and spencer), Khadi, Sapphire, Crimson, Suffuse by Sana Yasir for women clothing (Abrar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Luxury in Pakistan is usually defined by consumer possession of expensive and high-end branded cars, furniture, clothing, and eatery (Abrar et al, 2020). The country doesn't own many brands and industries, and most consumer products, including luxury cars, clothing, cosmetics, are imported from other countries such as Europe, America, China, and the Middle east (Mazahir et al, 2020). The data in this study will be collected from various consumers that aspire to, show a preference for, and buy or consume luxury brands in Pakistan.…”
Section: Introductionmentioning
confidence: 99%